Identifikasi Tipologi Wilayah Pengembangan Prasarana dan Sarana Dasar Pekerjaan Umum di Propinsi Daerah Istimewa Yogyakarta - Sri Rum Giyarsih (Journal of Regional and City Planning, 2000)
This article is based on research aiming at identifying typology of infrastructure development area in Yogyakarta Special Province. Data collecting is performed through field and institutional surveys. Field survey is carried out by means of direct observation and interviews to local people. Relevant institutions were visited in the period of institutional survey. Descriptive analysis is used in this study. The method to iden4fy the typology of infrastructure development area combines two versions of typology i.e. sub-district as economic growth (KPPE = Kecamatan sebagai Pusat Pertumbuhan Ekonomi) formulated by BAPPEDA and competitive sub-region (sub kawasan Andalan) proposed by Pusat Penelitian Perencanaan Pembangunan Nasiona l(P4N,) UGM The outcome of the research shows that in Yogyakarta Special Region there are eight typologies of basic infrastructure development area. These typologies are: Yogyakarta City (tipology 1); Pakem, Turi, Tempel (tipology 2); Kasihan, Piyungan, Prambanan, Godean, Mlati (tipology 3); Sedayu, Sentolo (tipology 4); Pundong, Imogiri, Srandakan, Kretek, Galur, Temon (tipologv 5); Kokap, Samigaluh (tipology 6); Ponjong, Semanu, Semin, Playen, Gedangsari (tipology 7); and Rongkap, tepus (tipology 8).